2002
DOI: 10.1148/radiol.2223010811
|View full text |Cite
|
Sign up to set email alerts
|

Crohn Disease with Endoscopic Correlation: Single-Shot Fast Spin-Echo and Gadolinium-enhanced Fat-suppressed Spoiled Gradient-Echo MR Imaging

Abstract: In patients with Crohn disease, gadolinium-enhanced fat-suppressed spoiled GRE MR imaging better depicted the extent and severity of intestinal disease compared with single-shot fast SE imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
110
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(128 citation statements)
references
References 26 publications
6
110
0
5
Order By: Relevance
“…Studies have confirmed the capability of MRI to detect fistulae and abscesses (6,7). Actively inflamed fistulous tracts and abscesses have been reported to have characteristic enhancement features on dynamic contrastenhanced MRI (8).…”
mentioning
confidence: 87%
“…Studies have confirmed the capability of MRI to detect fistulae and abscesses (6,7). Actively inflamed fistulous tracts and abscesses have been reported to have characteristic enhancement features on dynamic contrastenhanced MRI (8).…”
mentioning
confidence: 87%
“…Chronic inflammatory disease, and in particular, CD, represents the most common application of MRI of small bowel [1][2][3][4][5]8,9,15,[28][29][30][31][32][33][34][35]38] .…”
Section: Inflammatory Bowel Disease (Cd) (Figures 1-4)mentioning
confidence: 99%
“…Using shorter TE (60-90 m) can obtain simultaneous evaluation of fluids, bowel wall and surrounding structures. The use of fat saturation pulses is a useful complement to the acquisition of T2-weighted sequences [2,13,14,[29][30][31] . Fat saturation causes an increase in contrast between bowel wall and the surrounding fat tissue.…”
Section: Sequencesmentioning
confidence: 99%
See 2 more Smart Citations